Implementasi Program Peningkatan Kompetensi Guru Menuju Era Digitalisasi Pendidikan - Assa, Novel S.; Merentek, Risal M. (Jurnal Ilmiah Wahana Pendidikan, 2024)
The aim of this study is to describe and analyze the implementation of the enhancement of teacher skills program towards the era of digital education. Research method in this study is using library research method, to examine the theory, definition and concepts which is has the correlation with the main object. A technique of data analyzes is using content analysis method where we do the process of choosing, comparing, combining dan sorting the object until the data found relevan. The result of this study shows that: Firstly, Teachers must enchance their competences sustainability. Such as pedagogyc skills, personality skills, social skills and professional skills. So that the teacher can be ready to face the alteration toward the era of digital education; Secondly, to develop the potential belonging owned by the teachers, in order they can adapt with the progress of science and technology in digital era fluctuatively; Thirdly, in persuasive aspects, teachers can always practise themselve with education and training for career development, and prepare themselve to support the digital education in modern era. Fourthly, to strengthening the digital numeration and literation for teachers to simplify the effectiveness and efficiency of learning process among the students.